Developing mitigation strategies for the livestock sector in a collaborative approach across the Southern Cone - Gianoni, Cecilia (2025)
In collaboration of New Zealand Agricultural Greenhouse Gas Research Centre (NZAGRC), Inter-American Institute for Cooperation on Agriculture (IICA), Global Research Alliance on Agricultural Greenhouse Gases (GRA) and the Ministry for Primary Industries (MPI – New Zealand)